2021
DOI: 10.1029/2021jb022442
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Overspill Pyroclastic Density Currents in Sinuous Channels

Abstract: Due to their incredible mobility, even over substantial obstacles, pyroclastic density currents (PDCs) are a major hazard for people living around volcanic centers. Much of the uncertainty in the flow path of PDC is related to the interplay of topographic elements and a highly variable particle concentration field. As noted by simulations and inferences from deposits, PDCs are density stratified gravity currents and form a particle-concentrated underflow and an overriding dilute region sometimes referred to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 113 publications
(205 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the channelization of concentrated pyroclastic material allows reducing the energy dissipation rate, permitting the flows to reach larger distances than their non-channelized counterparts, and also enhances thermal insulation and thus promote hot overspills in unconfined areas at valleys bends (Kubo Hutchison and Dufek 2021). Different strategies have been adopted for the morphometric characterization of volcanoes (e.g., Pike 1978;Pike and Clow 1981;Grosse et al 2009Grosse et al , 2012Grosse et al , 2014 and a robust dataset is currently available in the literature (Grosse et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the channelization of concentrated pyroclastic material allows reducing the energy dissipation rate, permitting the flows to reach larger distances than their non-channelized counterparts, and also enhances thermal insulation and thus promote hot overspills in unconfined areas at valleys bends (Kubo Hutchison and Dufek 2021). Different strategies have been adopted for the morphometric characterization of volcanoes (e.g., Pike 1978;Pike and Clow 1981;Grosse et al 2009Grosse et al , 2012Grosse et al , 2014 and a robust dataset is currently available in the literature (Grosse et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Volcan de Fuego in 2018; Albino et al 2020). As detailed in Gueugneau et al (2021), Kubo Hutchison and Dufek (2021), and Lerner et al (2021), CPC overspills exhibit various depositional and dynamical characteristics, and here we distinguish two different types: (i) 'CPC overspill', when the concentrated basal layer of a CPC escapes the valley at a specific location, usually, but not always, accompanied by its upper ash-cloud surge. This overspill continues to flow along valley banks, volcaniclastic terraces and interfluves, and is usually named overbank flow to distinguish it from its parent valley-confined flow, as at Merapi during the 2006 or 2010 eruptions (Charbonnier and Gertisser 2008;Lube et al 2011;Gertisser et al 2012;Charbonnier et al 2013), at VolcĂĄn de Colima (Mexico) in 2015 (Macorps et al 2018) or at Fuego volcano in 2018 (Albino et al 2020) (Table 1).…”
Section: The Overspill Hazard Of Small-volume Cpcsmentioning
confidence: 72%
“…(a) a sharp valley bend (Ogburn et al 2014;Macorps et al 2018) (d) a sudden reduction of the valley width (i.e. constriction; Gertisser 2008, 2011;Jenkins et al 2013) Recently, Kubo Hutchison and Dufek (2021) and Gueugneau et al (2021) numerically studied the overspill mechanism. Kubo Hutchison and Dufek (2021) have demonstrated that a sinuous valley can cause an important increase of the local flow thickness along the outside of a bend, called superelevation, leading to the overspilling of the channelized flow.…”
Section: The Overspill Hazard Of Small-volume Cpcsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the mass flux increased, flow could no longer be contained within the channel at this site and it overflowed on the outside of the bend into the small San Miguel drainage, and followed a more direct path to the village, where its arrival was reported to have happened 10 min after the arrival of the block-and-ash flow at the Las Lajas bridge. This overflow, or partial avulsion, may have been aided by increased SSE momentum as the flow waxed, and also by localized thickening/ deepening of the flow as a result of oblique shock (HĂĄkonardĂłttir & Hogg, 2005) caused by the bend in the channel wall (Hutchison & Dufek, 2021). At the overflow site, the current was highly erosional, leaving longitudinal furrows.…”
Section: Flow Pulsing and Waxingmentioning
confidence: 99%